Legal Analysis of Police Challenges in Facing Transnational Cyber Crime - Rahmat Efendi Tanjung; Ahmad Ansyari Siregar; Nimrot Siahaan (International Journal of Science and Environment (IJSE), 2026)
The development of information technology has triggered an increase in transnational and increasingly complex cybercrimes. The cross-border nature of cybercrime poses serious challenges for law enforcement officials, particularly the Indonesian National Police (Polri), in the investigation, arrest, evidence-proving, and law enforcement processes. This study aims to analyze the legal challenges faced by the police in dealing with transnational cybercrime, including limited regulations, differences in jurisdiction between countries, difficulties in obtaining electronic evidence, limited technological and human resource capacity of the police, and limited international cooperation. Using a normative-juridical approach, this article finds that strengthening legal instruments, optimizing digital forensics, increasing investigator capacity, and intensifying international cooperation are strategic steps to increase the effectiveness of cybercrime countermeasures. In conclusion, the challenges faced by the police are multidimensional, requiring an adaptive, collaborative, and technology-based legal response. The normative-juridical approach is used to identify legal gaps based on the Criminal Procedure Code (KUHAP), the ITE Law No. 19 of 2016, and police regulations, which often hinder the collection of evidence and the determination of suspects due to victims being abroad. Recommendations include strengthening international cooperation, human resource training, harmonization of cyber regulations, and collaboration with the private sector for effective law enforcement in the digital era.